Increase in methane flux and dissociation of iron and manganese oxides recorded in a methane-derived carbonate nodule in the eastern margin of the Sea of Japan. (December 2016) - Hiruta, Akihiro; Klügel, Andreas; Matsumoto, Ryo
Abstract: High resolution analyses of an aggregate of aragonite crystals in a methane-derived carbonate nodule revealed evolution of interstitial water geochemistry associated with increases in methane flux at the Umitaka Spur gas seep site in the Sea of Japan. Geochemical data were obtained from the aggregate using Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), millimeter-scale powdering, and electron probe micro analysis. Most elements measured by LA-ICP-MS, and carbon and oxygen isotopic compositions (δ 13 C and δ 18 O, respectively) of aragonite, have symmetrical patterns in the aggregate. Concentrations of Ba, δ 13 CCaCO3, and δ 18 OCaCO3 increase monotonically towards the center of the aggregate (δ 13 CCaCO3 ; from –12 ‰ to –4 ‰VPDB), while rare earth elements (REEs) and Mn oscillate. Iron peaks are located closest to those of light REEs, and the shale-normalized pattern of a REE peak event is enriched in middle REEs, suggesting dissociation of Fe-oxides as the source of the REEs. The monotonically changing geochemical data and fan-shaped, acicular aragonites growing inwardly from the aggregate rim, suggest aggregate formation from rim to center. Therefore, the peak position of Mn to the interior of that of Fe, suggests an increase in dissolved Mn after the dissociation of Fe-oxides. The isotopic trends continue into the surrounding matrix, where δ 13 CCaCO3 reaches ∼–20 ‰VPDB, close to the δ 13 C of dissolved inorganic carbon currently found in the sulfate-methane transition (SMT). The trends of δ 13 CCaCO3 and Ba, and the evidence of dissociation of Fe-oxides suggest upward migration of the SMT during carbonate cementation, which is initiated in the SMT.